Strategi Kepala Madrasah Dalam Meningkatkan Nilai Tambah Bagi Siswa Era Society 5.0 - Nikma, Sulalatun; Asy’ari, Hasyim; Ratnaningsih, Sita (Universitas Muhammadiyah Gresik, 2023)
Education in the era of society 5.0 requires students to have significant added value, this problem indirectly requires teachers to have teaching skills with a digitalization system. This research method is qualitative-descriptive with a case study type. The results of the research show that the planning and implementation of added value in education in the era of Society 5.0 is through: 1) A strategy in decentralizing education through a performance-based PPDB system in all regions of Indonesia. 2) A strategy to reduce bipolarization through MASTAMA and Olympic and event-based career management. 3) Democratic education strategy through the integration of science and technology and imtak curricula as well as madrasah services in the form of workshops and outreach. 4) Strategies for community participation through madrasa committees. 5) Education strategy as an agent of change through the use of laptops, strong social attitudes and religiosity, e-learning systems and LMS, and homestay programs. The value-added model is increasing, as shown by the highest UTBK score in 2022 and the number of students entering PTN in 2023 is 78%. The obstacle experienced by the teachers is the lack of communication between the school teachers and the dormitory teachers, which has an impact on program delays that require coordination between the parties involved. The solution is for the madrasa director to open a line of communication between the school and the dormitory so that it can work well and smoothly. The conclusion of this study is that MAN Insan Cendekia Serpong conducts learning by focusing on the development of knowledge, adhering to religious values, and being a pioneer in social life.